Strategies for developing sustainable health research capacity in low and middle-income countries: a prospective, qualitative study investigating the barriers and enablers to locally led clinical trial conduct in Ethiopia, Cameroon and Sri Lanka. Issue 10 (13th October 2017) - Franzen, Samuel R P; Chandler, Clare; Siribaddana, Sisira; Atashili, Julius; Angus, Brian; Lang, Trudie
Abstract : Objectives: In 2013, the WHO stated that unless low-income and middle-income countries (LMICs) become producers of research, health goals would be hard to achieve. Among the capacities required to build a local evidence base, ability to conduct clinical trials is important. There is no evidence-based guidance for the best ways to develop locally led trial capacity. This research aims to identify the barriers and enablers to locally led clinical trial conduct in LMICs and determine strategies for their sustainable development. Design: Prospective, multiple case study design consisting of interviews (n=34), focus group discussions (n=13) and process mapping exercises (n=10). Setting: Case studies took place in Ethiopia (2011), Cameroon (2012) and Sri Lanka (2013). Participants: Local health researchers with previous experiences of clinical trials or stakeholders with an interest in trials were purposively selected through registration searches and snowball sampling (n=100). Primary and secondary outcome measures: Discussion notes and transcripts were analysed using thematic coding analysis. Key themes and mechanisms were identified. Results: Institutions and individuals were variably successful at conducting trials, but there were strong commonalities in the barriers and enablers across all levels and functions of the research systems. Transferable mechanisms were summarised into the necessary conditions for trial undertaking, which included: awareness of research, motivation, knowledge and technical skills, leadership capabilities, forming collaborations, inclusive trial operations, policy relevance and uptake and macro and institutional strengthening. Conclusions: Barriers and enablers to locally led trial undertaking exist at all levels and functions of LMIC research systems. Establishing the necessary conditions to facilitate this research will require multiple, coordinated interventions that seek to resolve them in a systemic manner. The strategies presented in the discussion provide an evidence-based framework for a self-sustaining capacity development approach. This represents an important contribution to the literature that will be relevant for research funders, users and producers.